Piama dan petua tradisi: Ilmu menanam padi masyarakat Melayu di utara semenanjung Malaysia - Rahimah A. Hamid, (Universiti Kebangsaan Malaysia, 2010)
The aim of this article is to discuss rice planting season and traditional precept as a knowledge of past paddy planters in rice planting. This research is done specifically in the northern part of Peninsular Malaysia, the states are Perlis, Kedah Darul Aman and Pulau Pinang. This research is done through fieldwork research, interviewing five paddy planters, going to the paddy fields, doing research at the paddy museum and library research on rice planting season and traditional precept. The works looked into are from Western writers as well as Eastern writers. The findings prove that past paddy planters used rice planting knowledge and traditional precept in carrying out work in their fields. This is due to the fact that in some societies rice is seen as pure or holy and is a staple for most of the world’s population. Due to the importance of paddy effort is made by planters to have a good yield. This research also shows that paddy planters are very sanative towards natural phenomenon and they learn from the universe. A phenomenon that occurs repeatedly when they plant paddy will be planted in the minds of the planters‘society and will form a body of knowledge about what to do and not to do during planting season. This knowledge is held and used so that the yield is rich. This is why there is special knowledge about rice planting. However the changing times and technological development has weakened the rice planting knowledge and traditional precepts that go against the religion have been left out of the lives of the paddy planters. This research is deemed important because it can be a sociocultural view of the paddy planting of past paddy planters to be made known to current society